RESOURCE-BASED COMMERCIAL FISHERIES MANAGEMENT IN EASTERN INDONESIA - Soepanto Soepanto (Indonesian Fisheries Research Journal, 1998)
Management may be defined as a way or strategy to attain set objectives. It is a system by which people are organized to meet certain purposes. Aside from people as the central element of management, there are also things, alive and dead, which are used in order to arrive at the set objectives.